Accessing, sharing and communicating agricultural information for development: Emerging trends and issues - Ballantyne, Peter G. (SAGE Publications, 2009)
The recent food crisis has helped to push agriculture and food security back on to national and development agendas. Additional international funds have been mobilized, national and regional initiatives have been strengthened, and a wide range of new and innovative instruments and approaches have been promised. Most of these efforts call for greater investment in knowledge creation, information access, and the wider use of information and communication technologies (ICTs). This paper explores what this renewed interest might mean for information and communication specialists working in agriculture. Starting from an ‘innovation systems’ perspective, it looks across the agricultural information for development landscape, highlighting some items on the agenda of information and communication specialists working in this area. Agenda items include: The widening recognition of the value of farmer knowledge, growing use of information and communication technologies (ICTs) to enable different agricultural development activities, concerns to ensure that public investments result in public goods whose benefits can travel, related efforts to ensure that agricultural content is open and accessible, the discovery and increasing use of a ‘social’ web, and some emerging new roles for agricultural library and information centers to meet changing demands.